2019
DOI: 10.1155/2019/5976540
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Deformation Characteristics of Long‐Short Pile Composite Foundation in Salt Lake Area, Iran

Abstract: To study the settlement and deformation characteristics of a long-short pile composite foundation and its influencing factors, the indoor centrifuge model test and numerical simulations were performed under the actual working conditions to treat the saline soft soil foundation in the Soltan salt lake area of Iran. Firstly, the settlement of a long-short pile composite foundation and the law of pile-soil stress ratio development with time were studied using a centrifuge model test. In addition, FLAC3D was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Assessing earlier research indicates that increasing the ratio of long to short pile length for a given length of long pile increases the pile-soil stress ratio of the short pile while reducing the same for the long piles [56]. On the other hand, the formation level of excavation with respect to the depth of pile tip affects the response of pile to neighbouring excavation [51], and for short piles as compared to long ones, excavation-induced pile settlement is likely to be a significant factor than lateral pile deflections [21].…”
Section: Effect Of Pile Tip Locationmentioning
confidence: 90%
“…Assessing earlier research indicates that increasing the ratio of long to short pile length for a given length of long pile increases the pile-soil stress ratio of the short pile while reducing the same for the long piles [56]. On the other hand, the formation level of excavation with respect to the depth of pile tip affects the response of pile to neighbouring excavation [51], and for short piles as compared to long ones, excavation-induced pile settlement is likely to be a significant factor than lateral pile deflections [21].…”
Section: Effect Of Pile Tip Locationmentioning
confidence: 90%
“…Qian and Zhang and Guo et al [13,14] showed that the infuence of a long pile on the overall settlement is greater than that of a short pile by diferent research methods. Based on the shear displacement method, Liu et al [15] studied the infuence of pile spacing on longshort pile composite foundation by the centrifugal model test and numerical simulation and put forward a reasonable range of pile spacing. Yang and Zhang [16] used fnite element analysis, a feld test, and the standard formula calculation method to analyze the infuence of cushion thickness, pile length, and raft thickness on the axial force and side friction resistance of long piles.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars introduced new analysis methods and examined the pile-soil composite foundation from different angles, thus improving traditional frameworks [19,20]. Furthermore, researchers conducted field tests [21][22][23] and indoor model tests [24,25] to obtain the working characteristics and evolution of the parameters of composite foundations under different geological conditions, different cushion thicknesses, and different pile conditions. e interaction between the rigid pile composite foundation and the base was analyzed.…”
Section: Introductionmentioning
confidence: 99%